Satellite based investigation for detection of ancient tombs’ looting in Cyprus - Agapiou, Athos; Lysandrou, Vasiliki (My University, 2016)
This study aims to present the results from the analysis of high resolution multispectral satellite and aerial images (WorldView-2) and RGB images from Google Earth© engine in order to map and diachronically monitor sites of archaeological interest that are endangered from looting. The research concerns the archaeological landscape of Ayios Mnason in Politico village, located in Nicosia district, where more than ten looted tombs have been identified. Some of these tombs have been disturbed in the past, while others by more recent illegal activities, detected in depth of more than three meters below ground surface. Image processing and in situ investigations evidenced that this phenomenon is not isolated, since other areas in the western part of the case study under examination in this paper, have been also disturbed. Overall, it is evident that image analysis and processing of high resolution multispectral satellite datasets, can be used for systematic monitoring of areas with archaeological interest, in order to protect and safeguard cultural heritage against illegal archaeological activities.
Keywords: Archaeological looting; Remote sensing; Aerial images; Satellite images; Cyprus; WorldView-2; Google Earth©